Soi-même comme un autre : James Agee et l’écriture documentaire de soi - Adriana HABEN (E-REA)
This paper analyzes James Agee’s only published novel, A Death in the Family. As an autobiographical novel published posthumously, it is a partially completed project in which Agee planned to insert photographs and to develop a form of writing focused on the factual and the real, with minimal resort to fiction. Eschewing a first-person narrative, he chooses to write using the third person, and to name the main character Rufus (after his own middle name). In studying this “documentary writing of the self,” we shall see how Agee strives to go beyond the limits between referentiality and fiction, and to avoid defining fiction purely as invention or imagination. We shall base our analysis on a comparison of two versions of the novel: the 1957 edition, and the 2007 edition revised and restored by Michael Lofaro, which contains previously unpublished chapters. We will point out the characteristics of this form of writing, from its close links to the visual arts (most notably photography) to the emphasis Agee puts on the depiction of scenes of everyday life. Thus, instead of being considered as a self-portrait of the artist as a young man, A Death in the Family can be read as a portrait of Agee through the eyes of his family.